Neurophysiological Evidence of Visual Cortical Alterations in Mild Primary Glaucoma: A Resting-State EEG Microstate Study - Rupesh Samanchi; Simran Kaur; Tanuj Dada; Ratna Sharma (Brain Topography, 2026)

Beyond a Biomarker: Hyperhomocysteinemia as a Metabolic-Inflammatory Amplifier and Pharmacological Target in Multisystem Disease - Arush Sharma; Swati Rana; Nishant Goutam; Simran Rana; Shiv Kumar Kushawaha; Mahendra Singh Ashawat (Indian Journal of Clinical Biochemistry, 2026)

Amine functionalized alumina supported metal–organic framework for wastewater treatment via adsorption and degradation of dyes; and for click reaction - Gunjan Vaid; Surbhi Sharma; Vrinda Sharma; Simran Gupta; Ritika Jaryal; Satya Paul (Environmental Science and Pollution Research, 2026)

Evaluation of Combinatorial Efficacy of Nisin and Lactoferrin against Pseudomonas Aeruginosa Induced Experimental Pulmonary Infection Model - Simran Preet; Jasleen Kaur; Anshul Panjeta; Shreya Dogra; Shivani Sharma (Current Microbiology, 2026)

RNA sequencing of the lncRNA regulome modulated by Withania somnifera in human neuroblastoma SK-N-SH cells - Eshita Sharma; Dilip Mehta; Simran Sahare; Saiprasad Ajgaonkar; Praful Saha; Anand Bhaskar; Jash Trivedi; Dhananya S.; Manju Moorthy; Gopalakrishna Ramaswamy; Sujit Nair (Molecular Biology Reports, 2025)
Background The dysregulation of long-chain noncoding RNAs (lncRNAs) causes several complex human diseases including neurodegenerative disorders across the globe. Methods and results This study aimed to investigate lncRNA expression profiles of Withania somnifera (WS)-treated human neuroblastoma SK-N-SH cells at different timepoints (3 & 9 h) and concentrations (50 & 100 µg/mL) using RNA sequencing. Differential gene expression analysis showed a total of 4772 differentially expressed lncRNAs, out of which 3971 were upregulated and 801 were downregulated compared to controls. Differential gene expression was observed in dose-dependent (30 upregulated, 25 downregulated, 100 µg/mL 3 h vs. 50 µg/mL 3 h; 36 upregulated, 247 downregulated, 100 µg/mL 9 h vs. 50 µg/mL 9 h) and temporal kinetics (79 upregulated, 64 downregulated, 50 µg/mL 9 h vs. 50 µg/mL 3 h; 22 upregulated, 200 downregulated, 100 µg/mL 9 h vs. 100 µg/mL 3 h). Enrichment analysis showed that modulated lncRNAs were mainly implicated in GPCR ligand binding, HDACs and HATs histones, cellular senescence, cell cycle and post-translational protein modifications. Dysregulated lncRNAs upon WS treatment included BACE1-AS, MALAT1, SNHG1, HOTAIR, MEG3, BDNF-AS, and SHANK2-AS1 which are potential biomarkers in several neurodegenerative diseases. Co-expression analysis revealed that genes such as HMOX1, CHGB, SLC7A11, NOS1, KCNJ and NPY2R may be important in neurodegenerative disorders. Conclusions Taken together, our results indicated that WS treatment modulated several differentially expressed lncRNAs with putative regulatory potential in various neurodegenerative disorders. To the best of our knowledge, the lncRNA regulome that elicits the health-beneficial effects of WS has not been delineated thus far.

Biology, demographic traits and predation rate of Cheilomenes sexmaculata (Fabricius) (Coleoptera: Coccinellidae) on peach leaf curl aphid, Brachycaudus helichrysi (Kaltenbach) (Hemiptera: Aphididae) - Aryan Bhandari; Chander Singh; Subhash Chander Verma; Prem Lal Sharma; Vishav Gaurav Singh Chandel; Rajeshwar Singh Chandel; Anshuman Semwal; Sushmita; Simran Sharma (Phytoparasitica, 2025)

Biology and life tables of the predatory mite (Neoseiulus longispinosus) on different developmental stages of the two-spotted spider mite (Tetranychus urticae) on carnation (Dianthus caryophyllus) cultivars - Pankaj Sharma; Vishav Gaurav Singh Chandel; Subhash Chander Verma; Prem Lal Sharma; Rajeshwar Singh Chandel; Nikita Chauhan; Chander Singh; Anshuman Semwal; Aryan Bhandari; Sushmita Goel; Simran Sharma; Shashank Kaundal (Experimental and Applied Acarology, 2025)

Biological Indices as Markers of the Health of Cirrhinus mrigala under the Stress of Microplastics and Metal Nanoparticles - Megha Andotra; Simran Sharma; Arvinder Kaur (Ecotoxicology, 2025)

Repercussion of colony conditions on attributes of Apis mellifera L. (Hymenoptera: Apidae) drones - Ojas Chauhan; Priyanka Thakur; Harish Kumar Sharma; Kiran Rana; Neha Negi; Simran Bhatia; Rakesh Kumar; Deeksha Sharma (International Journal of Tropical Insect Science, 2025)

Apple russeting-causes, physiology and control measures: A review - Naveen C. Sharma; Preetika Verma; Pramod Verma; Pramod Kumar; Chuni L. Sharma; Simran Saini (Planta, 2025)

Evaluation of chicory leaf extract on chronic kidney disease model in streptozotocin-induced diabetic nephropathy - Simran Sultana; Uday Raj Sharma; Reddibathina Leela Haripriya; Athira Ramachandran; Runashree Borah; V. Surendra; T. Haribabu; S. V. Gayathri; Suresh Janadri; P. M. Manjunatha (Advances in Traditional Medicine, 2024)

Ecosystem Health Assessment in India for Mainstreaming Global Biodiversity Framework Headline Indicator and Prioritising Conservation Action - Shalini Dhyani; Deepu Sivadas; Rajiv Chaturvedi; Amrita Neelakantan; Sonali Ghosh; Sarala Khaling; Simran Sharma; Dhritiman Das; Rajarshi Dasgupta (Anthropocene Science, 2024)

A systematic review on assessment of heavy metals toxicity in freshwater fish species: Current scenario and remedial approaches - Arvind Kumar Sharma; Munish Sharma; Simran Sharma; Davendra Singh Malik; Munit Sharma; Munish Sharma; Amit Kumar Sharma (Journal of Geochemical Exploration, 2024)

Critical review on the tetracycline degradation using photo-Fenton assisted g-C3N4-based photocatalysts: Modification strategies, reaction parameters, and degradation pathway - Simran Sharma; Anita Sudhaik; Sonu; Pankaj Raizada; Tansir Ahamad; Sourbh Thakur; Quyet Van Le; Rangabhashiyam Selvasembian; Van-Huy Nguyen; Ajay Kumar Mishra; Pardeep Singh (Journal of Environmental Chemical Engineering, 2024)

Diversity of bumble bees, their molecular analysis and first report of Bombus hypnorum L. (Hymenoptera: Apidae) from Himachal Pradesh - Kiran Rana; Ankur Rana; Sawraj Jit Singh; Simran Bhatia; Harish Kumar Sharma (Vegetos, 2024)

Synergistic improvement in electrochemical performance of Cr-doped MoS2/CuCo2S4 binary composite for hybrid supercapacitors - Pawanpreet Kour; Simran Kour; Deeksha; A.L. Sharma; Kamlesh Yadav (Fuel, 2024)

MyeloDB: a multi-omics resource for multiple myeloma - Ambuj Kumar; Keerthana Vinod Kumar; Kavita Kundal; Avik Sengupta; Simran Sharma; Kunjulakshmi R; Rahul Kumar (Functional & Integrative Genomics, 2024)

Strategic Approaches to Improvise Peptide Drugs as Next Generation Therapeutics - Panchali Barman; Shubhi Joshi; Sheetal Sharma; Simran Preet; Shweta Sharma; Avneet Saini (International Journal of Peptide Research and Therapeutics, 2023)

Enhancement of oxidative stability of soybean oil via nano-emulsification of eggplant peel extract: Process development and application - Simran Sharma; S. Chakkaravarthi; Bhaswati Bhattacharya (Food Chemistry, 2023)

Understanding the Intricate Role of Exosomes in Pathogenesis of Alzheimer’s Disease - Simran Chauhan; Tapan Behl; Aayush Sehgal; Sukhbir Singh; Neelam Sharma; Sumeet Gupta; Mohammed Albratty; Asim Najmi; Abdulkarim M. Meraya; Hassan A. Alhazmi (Neurotoxicity Research, 2022)

Accelerated Wound Healing Potential of Nisin in Streptozotocin Induced Diabetes Mellitus in Wistar Rats - Simran Preet; Shivani Sharma; Anshul Panjeta; Jasleen Kaur; Abdulrahman Alshammari; Metab Alharbi; Saud Almawash (International Journal of Peptide Research and Therapeutics, 2022)

Toxicological effects of marine seaweeds: a cautious insight for human consumption - Maushmi S. Kumar; Simran A. Sharma (Critical Reviews in Food Science and Nutrition, 2021)

Does valence influence perceptual bias towards incongruence during binocular rivalry? - Angel Anna Zacharia; Navdeep Ahuja; Simran Kaur; Nalin Mehta; Ratna Sharma (Cognitive Processing, 2020)

Evaluation of hexachlorocyclohexane contamination from the last lindane production plant operating in India - Simran Jit; Mandeep Dadhwal; Hansi Kumari; Swati Jindal; Jasvinder Kaur; Pushp Lata; Neha Niharika; Devi Lal; Nidhi Garg; Sanjay Kumar Gupta; Pooja Sharma; Kiran Bala; et al. (Environmental Science and Pollution Research, 2011)

Pseudomonas sp. to Sphingobium indicum: a journey of microbial degradation and bioremediation of Hexachlorocyclohexane - Rup Lal; Mandeep Dadhwal; Kirti Kumari; Pooja Sharma; Ajaib Singh; Hansi Kumari; Simran Jit; Sanjay Kumar Gupta; Aeshna Nigam; Devi Lal; Mansi Verma; Jaspreet Kaur; et al. (Indian Journal of Microbiology, 2008)